Sufistic Interpretation and its Influence in Islamic Spirituality: the Main characteristics of Sufistic Interpretation and its Method of Interpretation of the Verses of the Qur'an - Zaduna Fiddarain; Abdullah Mahmud; Andri Nirwana, A.N. (al-Afkar, Journal For Islamic Studies, 2024)
The main purpose of this study is to identify the main characteristics of Sufistic interpretation and analyze its methods of interpretation of Qur'anic verses as well as their influence on Islamic spirituality. The research method used is library research, which includes document analysis and literature review of works of sufistic interpretation, especially those written by figures such as Ibn Arabi and Jalaluddin Rumi. This study also involves a comparative analysis between sufistic interpretation and conventional interpretation to explore differences in approach and emphasis. The results of the study show that sufistic interpretation has two layers of meaning: the meaning of birth (zahir) and the meaning of the inner (bathin). The sharia dimension provides legal guidelines, while the Sufism dimension opens up space for deeper spiritual understanding. Methods of interpretation in sufistic interpretation, such as ta'wil and contemplation, allow individuals to not only understand the text intellectually, but also feel the Divine presence in their lives. This study found that Sufistic interpretation plays an important role in enriching Islamic spirituality, encouraging people to deepen their relationship with God and live the teachings of the Qur'an in a more personal and transformative way. The significance of this research lies in its contribution to broadening the horizons of Qur'anic interpretation, particularly from a sufistic perspective, as well as demonstrating the relevance of this approach in the spiritual life of Muslims in the contemporary era. This research is expected to provide inspiration for further research on the relationship between sacred texts and spiritual experiences in the Islamic tradition.